ANALYSIS OF FIQH SIYASAH TANFIDZIYAH ON THE IMPLEMENTATION OF WASTE REDUCTION POLICY IN WEST LAMPUNG - Putri Diana; Agustina Nurhayati; Rudi Santoso (Law Faculty of Universitas Bandar Lampung, 2025)
Waste reduction is the first step of waste management that affects the next waste management process. The waste problem really needs special attention from the Government and all elements of society because the waste problem has become a complex problem that must be addressed immediately. This study aims to analyse the Way Petai pekon government policy in waste reduction using the Siyasah Tanfidziyyah theory. The method used is a qualitative approach that is descriptive analysis, by conducting observations and interviews with the Pekon Way Petai Government and the Community. The results of this study show that several policies such as waste disposal regulations, socialisation and education related to waste and the provision of free trash boxes have been implemented by the Pekon Government. However, the implementation of these policies is not a long-term programme and there are still obstacles in its implementation, constrained by the location of waste bank construction sites and the lack of public awareness of the dangers of littering. The conclusion of this study confirms that the importance of Pekon government attention and long-term work programmes in the development of waste banks so that other policies can be implemented optimally.